In situ observation of fracture processes in high-strength concretes and limestone using high-speed X-ray phase-contrast imaging. (28th January 2017) - Parab, Niranjan D.; Guo, Zherui; Hudspeth, Matthew; Claus, Benjamin; Lim, Boon Him; Sun, Tao; Xiao, Xianghui; Fezzaa, Kamel; Chen, Weinong W.
Abstract : The mechanical properties and fracture mechanisms of geomaterials and construction materials such as concrete are reported to be dependent on the loading rates. However, the in situ cracking inside such specimens cannot be visualized using traditional optical imaging methods since the materials are opaque. In this study, the in situ sub-surface failure/damage mechanisms in Cor-Tuf (a reactive powder concrete), a high-strength concrete (HSC) and Indiana limestone under dynamic loading were investigated using high-speed synchrotron X-ray phase-contrast imaging. Dynamic compressive loading was applied using a modified Kolsky bar and fracture images were recorded using a synchronized high-speed synchrotron X-ray imaging set-up. Three-dimensional synchrotron X-ray tomography was also performed to record the microstructure of the specimens before dynamic loading. In the Cor-Tuf and HSC specimens, two different modes of cracking were observed: straight cracking or angular cracking with respect to the direction of loading. In limestone, cracks followed the grain boundaries and voids, ultimately fracturing the specimen. Cracks in HSC were more tortuous than the cracks in Cor-Tuf specimens. The effects of the microstructure on the observed cracking behaviour are discussed. This article is part of the themed issue 'Experimental testing and modelling of brittle materials at high strain rates'.